STRUKTUR KOMUNITAS MOLLUSCA PENEMPEL PADA VEGETASI MANGROVE DI PULAU KASU KECAMATAN BELAKANG PADANG KOTA BATAM - Firdaus, Ramses; Winarto, Noto; Dewi, Intan Sari (DIMENSI, 2014)
The purpose of this reaserch is to know about the structure of attached Mollusca community of mangrove vegetation. The vertical observation of the Mollusca here done to the root, stem and leares of the mangrove. The result of the research showed that Gastropoda that had been found consist of 8 (eight) Family and 11(eleven) species among any different mangrove vegetation. There were 7 kind of mangrove all and in the telly process the diversity, the similarity and domination index was vused. The mumber of Mollusca of every kind of vegetation were varied.While in morisite index the distribution fattern of the attached Mollusca were absolute defferent they distribution fattrent were random. The INP value of the every kind of mangrove is defferent the range between the lowest and the highest were about 27.859 to 300.000.